2019 IEEE/ACM 41st International Conference on Software Engineering: Software Engineering Education and Training (ICSE-SEET) 2019
DOI: 10.1109/icse-seet.2019.00012
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Entrepreneurial Experiences through a Software Engineering Project Course

Abstract: Skills and competencies in entrepreneurship, such as the ability to generate innovative ideas and the courage to engage with stakeholders and society, have gained importance in engineering curricula. In this case study paper, we report on how we have integrated entrepreneurial experiences into a software engineering project course and made the creation of value and reflection on the application of a structured process the heart and soul of the course. Based on current research on entrepreneurship education as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Burden et al [13] report a case study on how the integration of entrepreneurial experiences into a software engineering project course can benefit students to increase their teamwork skills and competencies. They discuss how to implement entrepreneurial experiences that focus on taking action and managing resources in agile software projects, making it possible to other SE educators to understand and even adopt specific course design aspects.…”
Section: Lesson #2: We Must Encourage Students To Use Their Communications Skills But It Is Recommended To Have a Plan B Just In Case O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Burden et al [13] report a case study on how the integration of entrepreneurial experiences into a software engineering project course can benefit students to increase their teamwork skills and competencies. They discuss how to implement entrepreneurial experiences that focus on taking action and managing resources in agile software projects, making it possible to other SE educators to understand and even adopt specific course design aspects.…”
Section: Lesson #2: We Must Encourage Students To Use Their Communications Skills But It Is Recommended To Have a Plan B Just In Case O Fmentioning
confidence: 99%
“…Working on real projects also support students to acquire entrepreneurial skills, such as communication, project management, and team-work. In this scenario, one of the challenges regarding the adoption of projects based on real-world problems is to find stakeholders with whom the students can cooperate and who are able and willing to invest necessary time and resources [12], [13]. Moreover, while entrepreneurship and PBL in SE education are burgeoning research topics, there seems to be very little work focusing on the pros and cons of involving external stakeholders in software engineering education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, there are also other reasons, like the necessity to tailor Individual Learning Plans, especially for students with special needs [39], although recent research showed that heterogeneous groups outperform homogeneous ones (also those composed by outstanding students) [19]. Surprisingly, educational approaches to convey computer science students with a broader set of skills (both of social and technical nature) are not rather uncommon in our community with few exceptions, such as [40,41]. Notably, Burden et al [41] provided insightful evidence, suggesting that Agile methods in project-based classes are an opportunity to experience entrepreneurial skills during software engineering classes.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Surprisingly, educational approaches to convey computer science students with a broader set of skills (both of social and technical nature) are not rather uncommon in our community with few exceptions, such as [40,41]. Notably, Burden et al [41] provided insightful evidence, suggesting that Agile methods in project-based classes are an opportunity to experience entrepreneurial skills during software engineering classes. The authors suggest that using Agile approaches in project-based courses stimulates opportunities for entrepreneurial experiences in software engineering courses, since they can be implemented in student projects to lead ideas into action.…”
Section: Background and Related Workmentioning
confidence: 99%